Phosphorus removal by a fixed-bed hybrid polymer nanocomposite biofilm reactor - Oliveira, M. (2014)
Eutrophication is one of the main challenges regarding the ecological quality of surface waters, phosphorus bioavailability being its main driver. In this context, a novel hybrid polymer nanocomposite (HPN-Pr) biofilm reactor aimed at integrated chemical phosphorus adsorption and biological removal was conceived. The assays pointed to removal of 1.2 mg P/g of reactive phosphorus and 1.01 mg P/g of total phosphorus under steady-state conditions. A mathematical adsorption–biological model was applied to predict reactor performance, which indicated that biological activity has a positive effect on reactor performance, increasing the amount of reactive phosphorus removed.